Broadband, Flat-Top, Silicon Photonic Contra-Directional Couplers Assisted by Asymmetric Multimode Photonic Crystals - Ronglei Sun; Qi Wang; Wenkang Wang; Rui Cheng (IEEE Photonics Journal, 2023)
Grating-assisted contra-directional couplers (CDCs) as 4-port wavelength-selective devices hold great potential as add-drop filters, multiplexers, routers, etc, for various integrated-optics applications. However, these devices have inherent low coupling strengths due to the coupled modes confined in different separate waveguides, preventing from realizing broad operation bands. Here, we propose silicon photonic CDCs assisted by novel asymmetric photonic crystals (APhCs) on multimode waveguides with elliptical nanoholes. Such APhC-assisted CDCs, compared with the conventional grating-assisted ones, can achieve significantly larger coupling strengths, thus offering much wider operation bands. We investigate the impact of changes in various structural parameters on the spectral response of an APhC-assisted CDC, and then discuss the design and optimization strategy of the device. The possibility of using other nanohole shapes of the APhC is also explored. In the experiments, a series of broadband and flat-top filters based on APhC-assisted CDCs on silicon-on-insulator (SOI) were fabricated and measured, and the influence of variations in the filter parameters on the response was validated. Notably, a 3 dB bandwidth of $\sim$ 48.8 nm was demonstrated on an APhC-assisted CDC with a coupling length of 22.3 um, which is the largest bandwidth ever reported for unchirped, SOI-based CDC filters, to the best of our knowledge.